2016
DOI: 10.1007/s12035-016-9982-3
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Recovery Characteristics of Five Common Anesthetics in Pediatric Anesthesia: a Network Meta-analysis

Abstract: Desflurane, halothane, isoflurane, propofol, and sevoflurane are widely used anesthetics in pediatric anesthesia. Adverse effect including emergence agitation, postoperative nausea and vomiting, and postoperative pain are common. Prolonged extubation time and emergency time are also troubling anesthesiologists. Previous studies have noted the characteristics of various anesthetics in pediatric anesthesia, while the results were inconclusive and conflicting. In this study, we aimed at performing a comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 71 publications
2
15
0
1
Order By: Relevance
“…Here, isoflurane at sub-anesthetic concentration induced hyperactivity in vivo. This is consistent with previous studies that sevoflurane can induce hyperactivity during induction and recovery (Costi et al, 2014;Guo et al, 2017;Liang et al, 2017). The isoflurane-induced hyperactivity was completely diminished in NALCN knockdown mice in vivo.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here, isoflurane at sub-anesthetic concentration induced hyperactivity in vivo. This is consistent with previous studies that sevoflurane can induce hyperactivity during induction and recovery (Costi et al, 2014;Guo et al, 2017;Liang et al, 2017). The isoflurane-induced hyperactivity was completely diminished in NALCN knockdown mice in vivo.…”
Section: Discussionsupporting
confidence: 93%
“…during anesthesia induction and recovery (Dahmani et al, 2010;Guo et al, 2017;Liang et al, 2017) and immobility at higher concentrations (Sonner et al, 2003). A variety of neuronal functions are bidirectionally modulated by volatile anesthetics (Chen et al, 2018;Yu et al, 2015;MacIver andRoth, 1987, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this discrepancy included the differences in the numbers of included studies and the participants undergoing different types of surgery, which involved different premedication types and the use of different tools to assess EA incidence. Moreover, in a recent study on desflurane, halothane, isoflurane, propofol, and sevoflurane in pediatric anesthesia, desflurane led to the highest EA incidence [32]. Our results indicated that dexmedetomidine use considerably decreased the EA incidence when patient received sevoflurane or desflurane.…”
Section: Plos Onesupporting
confidence: 56%
“…In a meta-analysis, Guo et al [10] investigated the effects of propofol, desflurane, halothane, isoflurane, and sevoflurane on agitation and recovery in pediatric cases, and recommended propofol as the most effective and safest anesthetic agent to provide pediatric anesthesia. Desflurane was reported to have the greatest incidence of agitation and the most difficult recovery characteristics.…”
Section: Discussionmentioning
confidence: 99%